2014
DOI: 10.1093/nar/gku198
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FANCD2 and FANCI monoubiquitination by their interaction and by DNA

Abstract: FANCD2 and FANCI function together in the Fanconi anemia network of deoxyribonucleic acid (DNA) crosslink repair. These proteins form the dimeric ID2 complex that binds DNA and becomes monoubiquitinated upon exposure of cells to DNA crosslinking agents. The monoubiquitinated ID2 complex is thought to facilitate DNA repair via recruitment of specific nucleases, translesion DNA polymerases and the homologous recombination machinery. Using the ubiquitin conjugating enzyme (E2) UBE2T and ubiquitin ligase (E3) FANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 32 publications
10
87
0
Order By: Relevance
“…UBE2T has been demonstrated to be the major E2 ubiquitin-conjugating enzyme required for the monoubiquitination of FANCD2 and FANCI (Alpi et al, 2008; Hodson et al, 2014; Longerich et al, 2014; Longerich et al, 2009; Machida et al, 2006; Sato et al, 2012). Efficient and specific FANCD2 monoubiquitination in vitro by UBE2T/FANCL requires the presence of FANCI and DNA (Longerich et al, 2014; Sato et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…UBE2T has been demonstrated to be the major E2 ubiquitin-conjugating enzyme required for the monoubiquitination of FANCD2 and FANCI (Alpi et al, 2008; Hodson et al, 2014; Longerich et al, 2014; Longerich et al, 2009; Machida et al, 2006; Sato et al, 2012). Efficient and specific FANCD2 monoubiquitination in vitro by UBE2T/FANCL requires the presence of FANCI and DNA (Longerich et al, 2014; Sato et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Kurumizaka and Sung laboratories demonstrated that several forms of DNA, including dsDNA, ssDNA, and Holliday junctions, could robustly stimulate the in vitro monoubiquitination of FANCD2. 45,56 Of note, this DNAdependent stimulation of FANCD2 monoubiquitination required both the presence of FANCI and its ability to bind to DNA. 56 Using Xenopus egg extracts, Sobeck and colleagues also demonstrated that the monoubiquitination of FANCD2 could be stimulated with linear and branched dsDNA structures but not with ssDNA or Y-shaped DNA.…”
Section: Fancd2 and Fanci: Dna Bindingmentioning
confidence: 97%
“…3,9,10,33 In vitro studies have also revealed that mutation of FANCD2 K561 leads to impaired FANCI monoubiquitination, whereas mutation of FANCI K523 has little effect on the monoubiquitination of FANCD2. 45 The E2 ubiquitin-conjugating enzyme and E3 ubiquitin ligase for FANCD2 and FANCI monoubiquitination are UBE2T and the RING domain-containing FANCL, respectively. 46,47 Biallelic mutations in the FANCL gene underlie the FA-L complementation group, however, FA patient-derived mutations in UBE2T have yet to be uncovered.…”
Section: Fancd2 and Fanci Monoubiquitinationmentioning
confidence: 99%
“…The p.Gln2Glu substitution abrogated FANCL monoubiquitination in vitro ( Figures 4D, S6B, and S6D); however, the FANCL-independent FANCI monoubiquitination was not affected ( Figure S6D). 12 These results are well explained by the specific disruption of the FANCL-UBE2T interaction by the p.Gln2Glu substitution.…”
mentioning
confidence: 84%
“…19) which has been implicated in this monoubiquitination reaction both in vivo 7-9 and in vitro. [10][11][12][13] We previously analyzed the ALDH2 genotypes in 64 Japanese FA-affected individuals with the approval of the Research Ethics Committee of the Tokai University Hospital and Kyoto University and obtained informed consent from the families of all subjects involved. 14 Our report included two case subjects in which mutations in the genes previously associated with FA were excluded by whole exome sequencing (WES) (listed as numbers 60 and 61 in Table S1 in Hira et al 14 ) ( Figure S1).…”
mentioning
confidence: 99%